The chosen one - Williams, Carol Lynch (New York : St. Martin's Griffin, 2009)
In a polygamous cult in the desert, Kyra, not yet fourteen, sees being chosen to be the seventh wife of her uncle as just punishment for having read books and kissed a boy, in violation of Prophet Childs' teachings, and is torn between facing her fate and running away from all that she knows and loves.
MSBA Nominee 2010-11.
Keywords: Cults -- Juvenile fiction; Polygamy -- Juvenile fiction; Families -- Juvenile fiction; Suspense fiction